Zbigniew Brzezinski papers : Part I - Brzezinski, Zbigniew, 1928-; Brzezinski, Zbigniew, 1928-
Correspondence, memoranda, speeches, writings, reports, notes, interview transcripts, press clippings, printed matter, photographs, and other papers relating primarily to Brzezinski's service as foreign policy advisor to Jimmy Carter's presidential campaign, assistant to the president for national security affairs, and official with the National Security Council. Documents his career at Columbia University, Harvard University, Trilateral Commission, and U.S. Department of State; work with the American-Ukrainian Advisory Committee; service as a foreign policy advisor to presidential candidates including Hubert H. Humphrey in 1968, several Democratic candidates in 1972, and George Bush in 1988; and his travels to China and former Soviet states as unofficial envoy of the Bill Clinton administration. Subjects include U.S.-Soviet relations; Sino-Soviet relations; East European communist states; Cold War and post-Cold War era; trilateral relationship between Japan, North America, and Western Europe; and role of the U.S. in world affairs. Drafts of Brzezinski's writings include his book, The Soviet Bloc: Unity and Conflict (1960). Correspondents include George Bush, Bill Clinton, Jerzy Giedroyc, William E. Griffith, Hubert H. Humphrey, Pope John Paul II, Henry Kissinger, Richard M. Nixon, Jan Nowak, and Henry Owen.
Foreign policy advisor, political scientist, educator, and author. Full name: Zbigniew Kazimierz Brzezinski.
Collection material in English, with Polish, Russian, French, and other foreign languages.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms Part I of the Zbigniew Brzezinski papers; cataloged in mm2003084951.
Keywords: Bush, George, -- 1924-; Bush, George, -- 1924- -- Correspondence; Carter, Billy; Carter, Jimmy, -- 1924-; Clinton, Bill, -- 1946-; Clinton, Bill, -- 1946- -- Correspondence; Giedroyc, Jerzy -- Correspondence; Griffith, William E. -- Correspondence; Humphrey, Hubert H. -- 1911-1978.; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; John Paul -- II, -- Pope, -- 1920-2005 -- Correspondence; Kissinger, Henry, -- 1923- -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Nowak, Jan, -- 1913- -- Correspondence; Owen, Henry, -- 1920-2011 -- Correspondence; United States. -- Department of State; American-Ukrainian Advisory Committee; Columbia University -- Faculty; Harvard University -- Faculty; National Security Council (U.S.); Trilateral Commission; Cold War; National security -- United States; Presidents -- United States -- Election -- 1968.; Presidents -- United States -- Election -- 1972.; Presidents -- United States -- Election -- 1976.; Presidents -- United States -- Election -- 1988.; China -- Foreign relations -- Soviet Union; China -- Foreign relations -- United States; Europe, Eastern -- History -- 1945-; Europe, Western -- Foreign relations -- Japan; Europe, Western -- Foreign relations -- North America; Former communist countries -- Foreign relations -- United States; Japan -- Foreign relations -- Europe, Western; Japan -- Foreign relations -- North America; North America -- Foreign relations -- Europe, Western; North America -- Foreign relations -- Japan; Soviet Union -- Foreign relations -- China; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- China; United States -- Foreign relations -- Former communist countries; United States -- Foreign relations -- Soviet Union; Authors; Educators; Political scientists; Presidential advisors